Volvulus of the Sigmoid Colon during Pregnancy: A Case Report - Enzo Fabrício Ribeiro Nascimento; Michelle Chechter; Fábio Piovezan Fonte; Nara Puls; Juliana Santos Valenciano; Cláudio Luciano Penna Fernandes Filho; Ronaldo Nonose; Crhistiny Emmanuelle Gabriel Bonassa; Carlos Augusto Real Martinez (Case Reports in Obstetrics and Gynecology)
Colonic obstruction due to sigmoid colon volvulus during pregnancy is a rare but complication with significant maternal and fetal mortality. We describe a case of sigmoid volvulus in a patient with 33 weeks of gestation that developed complete necrosis of the left colon. Case. 27-year-old woman was admitted with 3 days of abdominal distention, vomit, and the stoppage of the passage of gases and feces. She was admitted with poor clinical conditions with septic shock, acute respiratory distress syndrome, and signs of diffuse peritonitis. Abdominal radiography showed severe dilation of the colon with horseshoe signal suggesting a sigmoid volvulus, pneumoperitoneum and we could not we could not identify fetal heartbeats. With a diagnosis of complicate sigmoid volvulus she was underwent to the laparotomy where we found necrosis of all descending colon due to double twist volvulus of the sigmoid. We performed a colectomy with a confection of a proximal colostomy, and closing of the rectal stump. Due to an uncontrollable uterine bleeding during cesarean due, it was required a hysterectomy. The patient had an uneventful postoperative course thereafter and was discharged on a regular diet on the 15th postoperative day.